2012
DOI: 10.1371/journal.pone.0029928
|View full text |Cite
|
Sign up to set email alerts
|

ABO Blood Group and the Risk of Hepatocellular Carcinoma: A Case-Control Study in Patients with Chronic Hepatitis B

Abstract: BackgroundStudies have observed an association between the ABO blood group and risk of certain malignancies. However, no studies of the association with hepatocellular carcinoma (HCC) risk are available. We conducted this hospital-based case-control study to examine the association with HCC in patients with chronic hepatitis B (CHB).MethodsFrom January 2004 to December 2008, a total of 6275 consecutive eligible patients with chronic hepatitis B virus (HBV) infection were recruited. 1105 of them were patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 46 publications
(71 reference statements)
2
38
2
Order By: Relevance
“…In contrast with previous findings from a Chinese study (Li et al, 2012), our findings can be generalized to populations and are also applicable to hepatitis-free individuals. In our study, no statistically significant association was observed for the hepatitis patients, but blood group A showed a higher risk of HCC in hepatitisfree subjects.…”
Section: Discussioncontrasting
confidence: 75%
See 4 more Smart Citations
“…In contrast with previous findings from a Chinese study (Li et al, 2012), our findings can be generalized to populations and are also applicable to hepatitis-free individuals. In our study, no statistically significant association was observed for the hepatitis patients, but blood group A showed a higher risk of HCC in hepatitisfree subjects.…”
Section: Discussioncontrasting
confidence: 75%
“…Second, it has been reported that non-O blood group is an independent risk factor for the progression of liver fibrosis in HCV infection (Poujol-Robert et al, 2006). When compared with blood group O, subjects with blood group A tend to have more severely impaired liver function and earlier onset of cirrhosis (Li et al, 2012). This suggests an association between ABO blood groups and liver inflammation and fibrosis progression in patients with CHB.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations